Reuse of polyethylene scrap as building material for plastic waste minimisation / Haryani Azahari - Haryani , Azahari (2013)
This research focused on the application of polyethylene scrap material as modifier to enhance the properties in bitumen binder for the purpose of waste minimization. The prime objective of the study was to determine the optimum usage of scrap material in building material. Polyethylene modified bitumen was prepared by mixing and blending. The polyethylene content in the bitumen binder varied from 1, 3, 5, 7 and 10 percentage by weight. Polyethylene used is in pellet shape with 5mm of length. Four types of analysis consist of rheological, mechanical, chemical and surface morphology were conducted to study the effect of polyethylene content to bitumen binder characteristic. The polyethylene modified binder was analyzed with softening point test, penetration test, viscosity test and ductility test for conventional studies. Dynamic shear rheometer was used to study the effect of resistance to deformation and phase difference upon applied stress and resulting strain. A thermal degradation change was observed using thermogravimetric analyzer. The surface morphology was monitored using scanning electron microscope and optical microscope. Polyethylene modified binder was proven able to resist higher temperature before deformation and improved the resistance to fatigue cracking because of its stiffness Thermogravimetric studies showed that the thermal stability of polyethylene modified binder was improved compared to unmodified binder. Bitumen containing more than 5 percentage by weight polyethylene showed continuous polymer phase with dispersed bitumen. The transition of polymer network was observed by the decreasing of phase angle.